Positive childhood experiences and adult outcomes: A systematic review - Cunha, Olga (2024)
Although positive childhood experiences (PCEs) may serve as protective factors against the negative consequences of childhood adversity, they have been less extensively studied. However, more recently, there has been a growing interest in understanding the role of these experiences. This systematic review aims to address this research gap by systematizing the existing literature on PCEs and examining their relationship with both positive and negative outcomes. A comprehensive search of databases such as B-On, PsycINFO, PubMed, SCOPUS, and Scielo identified 87 studies that met the inclusion criteria. Different studies have employed various designs and samples to investigate the relationship between PCEs and adult outcomes. The findings suggest that higher levels of PCEs are consistently associated with better mental health outcomes, such as decreased depressive symptoms, anxiety, and suicidal behaviors, as well as improved psychosocial well-being, including reduced perceived stress and increased life satisfaction. Conflicting results were found for behavioral outcomes, physical health, stressful life events, and parenting and family functioning. In addition, the interaction effect of PCEs on adverse childhood experiences (ACEs) in adulthood is inconsistent. PCEs and ACEs appear to be independent sets of experiences that often coexist, with PCEs frequently not moderating the consequences of adversity on outcomes. More research with diverse samples is needed to better understand the role of PCEs.